Knowledge regarding Human Milk Banking and its Acceptability among Mothers at Bharatpur Hospital, Chitwan, Nepal (International Journal of Silkroad Institute of Research and Training, 2024)
Background: Human milk banking is a system that collects, processes, stores and donated breast milk to infants whoare unable to receive breast milk from their biological distributes mothers. It promotes optimal nutrition and health forvulnerable infants, particularly those who are premature, ill or have special medical conditions. This study aimed to assessthe knowledge regarding human milk banking and its acceptability among mothers at Bharatpur Hospital, Chitwan, Nepal.Method: A hospital based descriptive cross-sectional study carried out among 135 mothers admitted at postnatal ward ofthe hospital. Data collected from June 15 to July 15, 2023 by using structured interview questionnaires. All collected dataentered and analyzed using statistical package for social sciences (SPSS) to assess the knowledge regarding human milkbanking and its acceptability among mothers.Result: The finding revealed that the mean age of respondents was 26.27(±4.92) year. Nearly half of respondents (49.6%)had average knowledge, 43% had poor knowledge, and only 7.4% had adequate knowledge regarding human milk banking.Likewise, most of (70.4%) the respondents expressed their acceptability toward human milk banking. There was significantassociation between ethnicity and level of knowledge. The level of knowledge was strongly correlation (r=0.846, p=